A maturity model for Clinical Trials Management Ecosystem - Shruti Sehgal; E. Chris Pua; Svetlana Rojevsky; Michael J. Becich; Joshua Fehrmann; Boyd M. Knosp; Adam Wilcox; Jeffery C. Talbert; Catherine K. Craven; Justin Starren (Journal of Clinical and Translational Science)
Abstract